Density functional theory investigation of site predilection of Fe substitution in barium titanate - Piyarat Nimmanpipug (2018)
The site predilection and effects of the impurity in the form of Fe (II) and Fe (III) in the tetragonal barium titanate lattice were systematically determined by density function theory calculations. All electron calculation was carried out in the local density approximation (LDA). It is shown that both Fe (II) and Fe (III) prefer to substitute at the titanium site with oxygen vacancy compensation as a result of lowest substitution energy. Effect of Fe dopant both in form of Fe (II) and Fe (III) at titanium site with oxygen vacancy compensation lead to change in electrical property in terms of energy band structure of the tetragonal barium titanate lattice. © 2012 Elsevier Ltd and Techna Group S.r.l.